Determining the burden of foodborne hepatitis A spread by food handlers: suggestions for a targeted vaccination? - Cecilia Trucchi; Filippo Del Puente; Carolina Piccinini; Marco Roveta; Marina Sartini; Marina Sartini; Maria Luisa Cristina; Maria Luisa Cristina (Frontiers in Public Health)
IntroductionHepatitis A virus (HAV) remains a significant foodborne pathogen, particularly when food handlers serve as the source of contamination. Its high infectivity and environmental persistence allow the virus to survive on hands, surfaces, and food, facilitating widespread transmission even from a single distribution point.MethodsThis systematic review, Prospero registration number: CRD420250651930, analyzed 32 studies reporting HAV outbreaks linked to food handlers to assess whether vaccination could be an effective preventive strategy.ResultsMost outbreaks occurred in North America and Europe, with index cases almost exclusively identified among food workers. Outbreak sizes varied, though the majority involved fewer than 50 cases.DiscussionStudies highlighted critical challenges, including underreporting, asymptomatic cases, and delayed interventions. Control measures largely relied on immunoglobulin administration, while vaccination was rarely implemented and showed poor adherence among food service staff. Although economic analyses were limited and sometimes inconclusive, some evidence suggested potential healthcare savings from prevention efforts. Considering HAV’s high transmissibility and the difficulty of timely outbreak detection, targeted vaccination of food handlers—especially those in high-risk settings or seasonal employment—emerges as a promising method of biological risk management in food industries. These considerations could support food industries in considering vaccination as a tool to prevent foodborne HAV transmission.